2022
DOI: 10.1093/eurheartj/ehab918
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity cardiac troponin I after coronary artery bypass grafting for post-operative decision-making

Abstract: Aims Current troponin cut-offs suggested for the post-operative workup of patients following coronary artery bypass graft (CABG) surgery are based on studies using non-high-sensitive troponin assays or are arbitrarily chosen. We aimed to identify an optimal cut-off and timing for a proprietary high-sensitivity cardiac troponin I (hs-cTnI) assay to facilitate post-operative clinical decision-making. Methods and results We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
16
0
4
Order By: Relevance
“…Similarly, in our study, only the level of CK-MB from CS after cross-clamping was significantly lower in the IBC compared with the HTK group while no difference was seen with cTnI in comparison. For that reason, as the sensitivity and specificity of cTn are superior to CK-MB, 16 this finding could not be enough to talk about the superiority of one solution over another in our opinion.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, in our study, only the level of CK-MB from CS after cross-clamping was significantly lower in the IBC compared with the HTK group while no difference was seen with cTnI in comparison. For that reason, as the sensitivity and specificity of cTn are superior to CK-MB, 16 this finding could not be enough to talk about the superiority of one solution over another in our opinion.…”
Section: Discussionmentioning
confidence: 88%
“…Our data showed that outcome in patients who required post-operative coronary angiography after tricuspid surgery was significantly worse. Post-operative coronary angiography is mostly performed due to hemodynamic instability, post-operative ST-segment elevation, significantly elevated levels of cardiac markers or due to ventricular wall motion disorders in echocardiography indicating myocardial ischemia ( 10 ). In some patients, in particular in patients with concomitant left-sided valve procedure, coronary interventions on the left coronary artery were necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although the requirement for supporting findings is a widely debated topic, and recent pivotal studies have refuted an association of isolated peak biomarker release-based definitions and impaired prognosis, 12,16 the need for supporting ECG and imaging evidence is beyond the scope of the current review.…”
Section: Heterogeneity In Definitions Of Periprocedural Myocardial In...mentioning
confidence: 97%
“…15 Biomarker measurements are the cornerstone of the diagnosis of PMI, but supporting evidence might be crucial. 12,16 These supporting findings comprise either ECG or imaging findings. Especially in studies evaluating postoperative cTn values with delayed enhancement cardiac magnetic resonance (DE-CMR) follow up, the amount of myocardial injury identified by DE-CMR was correlated with peak cTn and predictive of adverse prognosis.…”
Section: Heterogeneity In Definitions Of Periprocedural Myocardial In...mentioning
confidence: 99%
See 1 more Smart Citation